Comparison of severe on‐farm injuries to older and younger persons in New South Wales (2012‐2016). (20th June 2021) - Walker, Jarrod; Lower, Tony; Peachey, Kerri‐Lynn
Abstract: Objectives: To assess and compare rates of severe on‐farm injury for older (> 50 years) and younger (15‐49 years) cohorts, on NSW farms. Design: Descriptive retrospective epidemiological study of the New South Wales Trauma Registry (Institute of Trauma and Injury Management ‐ ITIM) for persons injured on a farm. Setting: New South Wales, Australia. Participants: Cases involving persons (≥15 years), with data on the NSW Trauma Registry (2012‐16). Main outcome measures: Comparison of injury rates and severity between younger (15‐49 years) and older (50+ years) cohorts over the 2012‐16 period based on Injury Severity Scores (ISS). Results: Older males are injured at a rate that is roughly 18% higher than younger males and 13% higher than the overall injury rate. Older individuals also have significantly longer hospital stays post‐injury ( P = 0.01), with this being most pronounced for older men ( P < 0.01). There was no statistically significant difference in ISS demonstrated between the age cohorts ( P = 0.64), except for younger women having higher median ISS than their older female counterparts ( P = 0.02). Conclusion: Overall, the general trends displayed support the contention that older males are more likely to incur a severe on‐farm injury than their younger counterparts. This provides support for a preventative focus targeting older farmers in NSW.